Gene Probes Principles and Protocols - Aquino do Muro, Marilena.; Aquino do Muro, Marilena.; Rapley, Ralph.; Rapley, Ralph. (Methods in Molecular Biology, 2002)
The use of nucleic acid or gene probes as cloning or diagnostic tools has promoted significant advances in human genome mapping and in the isolation and manipulation of genes generally. In Gene Probes, Marilena Aquino de Muro and Ralph Rapley have brought together an outstanding collection of time-tested protocols for designing and using gene probes in a wide variety of applications. The applications covered range from searching for specific genes in the human chromosome to the detection of microorganisms and their toxins in the environment and in food samples, as well as in the diagnosis of human disease. Each cutting-edge method includes practical hints and tips and is described in step-by-step detail by an expert who not only routinely uses the technique, but has also optimized it for experimental success. Helpful tutorials explain the principles of gene probe design, labeling, detection, target formation, and hybridization conditions. Comprehensive and versatile, Gene Probes: Principles and Protocols provides a cutting-edge practical resource for all biochemists, microbiologists, and molecular biologists who are using this powerful new technology to advance medical, environmental, and food research today.